2016
DOI: 10.1101/gad.277483.116
|View full text |Cite
|
Sign up to set email alerts
|

LRH-1-dependent programming of mitochondrial glutamine processing drives liver cancer

Abstract: Various tumors develop addiction to glutamine to support uncontrolled cell proliferation. Here we identify the nuclear receptor liver receptor homolog 1 (LRH-1) as a key regulator in the process of hepatic tumorigenesis through the coordination of a noncanonical glutamine pathway that is reliant on the mitochondrial and cytosolic transaminases glutamate pyruvate transaminase 2 (GPT2) and glutamate oxaloacetate transaminase 1 (GOT1), which fuel anabolic metabolism. In particular, we show that gain and loss of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
66
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(71 citation statements)
references
References 30 publications
5
66
0
Order By: Relevance
“…Supplementations in vivo with an α-KG analog that rescued mTORC1 activity and prevented ammonia-induced autophagy provide robust evidence for an α-KG-dependent modulation of hepatic mTORC1 activity during hyperammonemia. Hence, our data are consistent with previous studies showing a direct correlation between α-KG levels and mTORC1 activity (20,24,(47)(48)(49). The activity of the oxygen sensors EGLN/prolyl hydroxylases that require oxygen and α-KG for hydroxylation of target proteins has been proposed to explain α-KG-dependent activation of mTORC1 (48).…”
Section: Discussionsupporting
confidence: 92%
“…Supplementations in vivo with an α-KG analog that rescued mTORC1 activity and prevented ammonia-induced autophagy provide robust evidence for an α-KG-dependent modulation of hepatic mTORC1 activity during hyperammonemia. Hence, our data are consistent with previous studies showing a direct correlation between α-KG levels and mTORC1 activity (20,24,(47)(48)(49). The activity of the oxygen sensors EGLN/prolyl hydroxylases that require oxygen and α-KG for hydroxylation of target proteins has been proposed to explain α-KG-dependent activation of mTORC1 (48).…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, another target can be the liver receptor homolog (LRH-1), implicated in coordinating glutamine-induced metabolism and hepatocarcinogenesis. Xu et al demonstrated that LRH-1 deletion inhibited HCC cell proliferation through different mechanism, such as reduction of glutamine deamination and glutaminolysis and inhibition of mTOR signaling [171].…”
Section: Targeting Glutaminementioning
confidence: 99%
“…Glucose transport, metabolism, and capture are regulated by LRH-1 via control of proteins such as the GLUT4 transporter in skeletal muscle and glucokinase in the liver (Oosterveer et al, 2012;Bolado-Carrancio et al, 2014). On the other hand, aberrant activation of LRH-1 drives tumorigenesis and tumor-cell proliferation in several cancer types (Chand et al, 2010;Thiruchelvam et al, 2011;Bianco et al, 2014;Lin et al, 2014;Bayrer et al, 2015;Nadolny and Dong, 2015;Xu et al, 2016). Because of this vital transcriptional program, LRH-1 is garnering attention as a new therapeutic target for treatment of diseases such as nonalcoholic fatty liver disease, diabetes, and cancer.…”
Section: Introductionmentioning
confidence: 99%